Evolution of agricultural mechanization in Viet Nam - Takeshima, Hiroyuki; Liu, Yanyan; Cuong, Nguyen Van; Masias, Ian (International Food Policy Research Institute, 2020)
Despite the reportedly rapid growth of mechanization, as well as its unique history in economic and social systems, information on the patterns of agricultural mechanization growth in Viet Nam has been limited. Through an extensive review of existing literature and several rounds of nationally representative household survey data, we document the evolution of mechanization (particularly with tractors and combine harvesters) in Viet Nam, including the heterogeneity across regions and farm sizes, and the emerging roles of the private sector in the supply of machinery and hiring services. The historical growth pattern of mechanization in Viet Nam had been nonlinear, characterized by somewhat high tractor use prior to 1975, followed by a decline in the 1980s before a resurgence in the 1990s, with considerable variations in adoption patterns across regions. Since the economic and social reform in the late 1980s, the private sector has rapidly emerged as the major player in meeting the demand for greater farm power uses, including the domestic manufacturing of power tillers, the introduction of larger combine harvesters, and the emergence of individual machine owners as the primary suppliers of hiring services. Although machinery use has gradually spread from larger farms to smaller farms, there are some signs that the comparative advantage has been shifting toward larger farms.